Analysis of foreign direct investments and its’ impact on restructuring of Lithuanian economy - Tvaronavičienė, Manuela; Ginevičius, Romualdas (Journal of Business Economics and Management, 2003)
The paper deals with foreign direct investments (FDI) in Lithuania. An issue of priority is to determine if inflow of foreign capital in all cases contributes sufficiently to development of national economy. Investigation of controversial impact of FDI on Lithuania is based on theories presented by concise review of the literature examining the role of FDI in transition economies. The detailed analysis of FDI directed to different sectors of Lithuanian economy let to determine cases when globalization retards economic development of host country.First Published Online: 14 Oct 2010